2017
DOI: 10.1016/j.biopsych.2016.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Translating the Habenula—From Rodents to Humans

Abstract: The habenula (Hb) is a central structure connecting forebrain to midbrain regions. This microstructure regulates monoaminergic systems, notably dopamine and serotonin, and integrates cognitive with emotional and sensory processing. Early preclinical data have described Hb as a brain nucleus activated in anticipation of aversive outcomes. Evidence has now accumulated to show that Hb encodes both rewarding and aversive aspects of external stimuli, thus driving motivated behaviors and decision-making. Human Hb re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
130
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 141 publications
(133 citation statements)
references
References 115 publications
(144 reference statements)
2
130
1
Order By: Relevance
“…Glutamatergic LHb neurons are transiently activated by aversive stimuli including acute stressors 89, 90 and exert a feedforward inhibitory influence on the activity of midbrain dopamine neurons by virtue of their connections with GABAergic cells in the rostromedial tegmental area 9193 . Activation of LHb neurons is also associated with depression-related phenotypes in animal models 9496 and in patients with MDD 88, 97 . It has been recently demonstrated that LHb neurons show enhanced burst activity in rats characterized by congenital helpless behavior 98 .…”
Section: Nmdar Inhibition-mediated Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation
“…Glutamatergic LHb neurons are transiently activated by aversive stimuli including acute stressors 89, 90 and exert a feedforward inhibitory influence on the activity of midbrain dopamine neurons by virtue of their connections with GABAergic cells in the rostromedial tegmental area 9193 . Activation of LHb neurons is also associated with depression-related phenotypes in animal models 9496 and in patients with MDD 88, 97 . It has been recently demonstrated that LHb neurons show enhanced burst activity in rats characterized by congenital helpless behavior 98 .…”
Section: Nmdar Inhibition-mediated Mechanismsmentioning
confidence: 99%
“…The lateral habenula (LHb) is a highly conserved region of the epithalamus that acts as an intermediary between the forebrain, and midbrain monoaminergic systems 87, 88 . Glutamatergic LHb neurons are transiently activated by aversive stimuli including acute stressors 89, 90 and exert a feedforward inhibitory influence on the activity of midbrain dopamine neurons by virtue of their connections with GABAergic cells in the rostromedial tegmental area 9193 .…”
Section: Nmdar Inhibition-mediated Mechanismsmentioning
confidence: 99%
“…The lateral habenula, in particular, is notable for receiving inputs from the basal ganglia and limbic system and projecting broadly to dopaminergic and serotonergic neurons in the midbrain. During the past 20 years, a number of studies—as reviewed by Boulos and colleagues in this issue (3)—are increasingly suggesting a novel, circuit-based paradigm through which the habenula may be causally involved in the onset of depression and other psychiatric illnesses.…”
mentioning
confidence: 99%
“…Specifically, increased activity in the lateral habenula (LHb) increases activity in the ventral tegmental area (VTA), potentiating projections to the nucleus accumbens medium spiny neurons and weakening projections to the medial prefrontal cortex (mPFC) 65 . Evidence is now accumulating that the habenula is acting as a "disappointment" center of the brain, with neurons in this region being excited in the absence of reward and inhibited in rewarding situations [66][67][68][69] . Animal models displaying depressive behavior also show increased activation of lateral habenular neurons, in turn feeding to excite the VTA [70][71][72] .…”
Section: The Circuitry Of Depressionmentioning
confidence: 99%
“…Animal models displaying depressive behavior also show increased activation of lateral habenular neurons, in turn feeding to excite the VTA [70][71][72] . Moreover, experiments involving deep brain stimulation of the habenula in both rats and humans were able to reduce neuronal activity and improve depressive symptoms 69,70 .…”
Section: The Circuitry Of Depressionmentioning
confidence: 99%